Evaluation of Candida glabrata for Simultaneous Saccharification and Fermentation (SSF) of Total Sago Effluent - Queentety, Johnny (Universiti Malaysia Sarawak (UNIMAS), 2021)
Sago palm plantations are mostly found in Sarawak and the sago industries have produced tons of wastes every year. These sago wastes could be potential biomass substrate for bioethanol production as it can be found abundantly. In bioethanol production, the ability of microorganisms to ferment substrate is important to achieve high ethanol yield. Candida glabrata is commonly found in fermented foods such as ragi and can potentially be used as a fermentative organism in bioethanol production. Hence, in this study, C. glabrata was evaluated to convert carbohydrate substrates to ethanol. The first objective of the study was evaluation of C. glabrata in production of ethanol from simple sugar such as glucose, maltose and sucrose. Fermentation process was carried out for 5 days, with 150 rpm at ambient temperature. Results indicated that C. glabrata only consumed glucose and sucrose with the maximum ethanol production of approximately 20.4 g/l and 1.64 g/l, respectively. Among these sugars, C. glabrata yielded the highest ethanol content in glucose substrate. This showed that C. glabrata could be a potential fermentative organism since it can ferment glucose efficiently. Next, the fermenting capability of C. glabrata was evaluated on complex sugars such as soluble starch and cellulose powder. Results showed that C. glabrata capable of fermenting soluble starch and cellulose powder only with the aid of enzymes (amylases and cellulases). In the absence of enzymes, there was no ethanol produced. This indicated that C. glabrata does not produce amylolytic enzymes that breakdown starch. C. glabrata also unable of breaking down cellulose and requires extracellular cellulase to convert cellulose into fermentable sugar. In the last objective, C. glabrata was subjected to Simultaneous Saccharification and Fermentation (SSF) using total sago effluent as a biomass feedstock. Prior to the SSF, compositional analysis steps were conducted. Based on the results, total sago effluent was comprised 97.14 ± 0.09% sago hydrolysate and 2.86 ± 0.09% solid component (sago hampas). Further compositional analysis was carried out, and it was found that sago hydrolysate was containing 2.23 ± 0.86% starch while sago hampas was composed of 52.03 ± 1.11% starch, 27.82 ± 0.62% cellulose, 5.32 ± 0.96% hemicellulose, 3.00 ± 0.05% lignin and 1.95 ± 0.03% ash. SSF was conducted on total sago effluent for 5 days with the aid of enzymes (amylases and cellulases) and C. glabrata as a fermenting organism in a working volume of 150 ml. Results showed that the highest ethanol production was detected at 24 h, with a yield of 5.44 g/l. This indicated that C. glabrata could be used in bioethanol production because it can grow on lignocellulosic substrate such as total sago effluent. During the SSF, C. glabrata was found to be incapable of fermenting xylose and arabinose, thus resulting in low ethanol yield. Overall, C. glabrata has high fermentative activity for glucose, with 79.84% of theoretical yield which makes it highly suitable candidate for glucose fermentation. However, C. glabrata was incapable of fermenting other substrates efficiently as glucose since it only yielded low ethanol content for both sucrose and total sago effluent. Therefore, it can be concluded that C. glabrata is inefficient and unsuitable for industrial bioethanol processes. The efficiency and productivity of ethanol can be enhanced by performing genetic modification to increase the range of consumed sugars by C. glabrata.